Robust sliding mode control for discrete delayed systems with randomly varying nonlinearities under uncertain occurrence probability - Panpan Zhang; Jun Hu; Hongxu Zhang; Dongyan Chen (2017 Chinese Automation Congress (CAC), 2017)
In this paper, the problem of robust sliding mode control is studied for a class of discrete delayed nonlinear systems subject to randomly varying nonlinearities (RVNs) under uncertain occurrence probability. Here, the time-varying delay is bounded with known upper and lower bounds. The RVNs under uncertain occurrence probability are characterized by utilizing a Bernoulli distributed random variable, where the occurrence probability could be uncertain with hope to better reflect engineering reality. The aim of the paper is to provide a sliding mode control method such that the robust exponential stability of the sliding mode dynamics is guaranteed, which is in the form of linear matrix inequalities (LMIs) and an equality constraint. Moreover, the robust sliding mode controller is synthesized to drive the system states onto a neighborhood of pre-designed sliding mode surface, i.e., the reaching condition can be ensured simultaneously. Finally, we show the effectiveness of proposed SMC technique by using a simulation example.